2015
DOI: 10.1038/nn.3973
|View full text |Cite|
|
Sign up to set email alerts
|

Retrieval induces adaptive forgetting of competing memories via cortical pattern suppression

Abstract: Remembering a past experience can, surprisingly, cause forgetting. Forgetting arises when other competing traces interfere with retrieval, and inhibitory control mechanisms are engaged to suppress the distraction they cause. This form of forgetting is considered adaptive because it reduces future interference. The impact of this proposed inhibition process on competing memories has, however, never been observed both because behavioural methods are “blind” to retrieval dynamics and because neuroimaging methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
213
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(253 citation statements)
references
References 46 publications
22
213
1
Order By: Relevance
“…Further in line with this, Karlsson Wirebring et al [31] reported a decrease in activity of the left DLPFC over the course of repeated successful practice-testing which was predictive of better later memory performance. Similarly, in the previously mentioned retrieval-induced forgetting study by Wimber et al [37], activity in the left and right VLPFC decreased over the course of repeated selective retrieval. Moreover, activations predicted how much competing information was suppressed but not how much target information was enhanced: more activation in the left and right VLPFC during the retrieval of specific memories predicted stronger suppression of that memory's competitors.…”
Section: The Role Of Mental Effort During Retrievalsupporting
confidence: 70%
See 3 more Smart Citations
“…Further in line with this, Karlsson Wirebring et al [31] reported a decrease in activity of the left DLPFC over the course of repeated successful practice-testing which was predictive of better later memory performance. Similarly, in the previously mentioned retrieval-induced forgetting study by Wimber et al [37], activity in the left and right VLPFC decreased over the course of repeated selective retrieval. Moreover, activations predicted how much competing information was suppressed but not how much target information was enhanced: more activation in the left and right VLPFC during the retrieval of specific memories predicted stronger suppression of that memory's competitors.…”
Section: The Role Of Mental Effort During Retrievalsupporting
confidence: 70%
“…More direct investigations of changes in memory representations over time have recently become available from two publications that apply multivariate analysis techniques to the study of repeated retrieval [31,37]. Karlsson Wirebring et al [31] used representational similarity analysis [RSA; 38] to correlate patterns of brain activation between multiple trials to determine under which conditions brain activations are more similar or dissimilar from each other.…”
Section: How Does Testing Affect Memory Representations?mentioning
confidence: 99%
See 2 more Smart Citations
“…First, rehearsal of a subset of the videos may inhibit consolidation of the nonrehearsed set and this inhibition may result in unrehearsed videos being largely forgotten ("retrievalinduced forgetting") (Anderson et al, 2000;Wimber et al, 2015). Although this explanation does not explain why active rehearsal is such a good method for retention of detail over long periods (Roediger and Karpicke, 2006), it may explain why recall for nonrehearsed videos was so poor.…”
Section: Discussionmentioning
confidence: 99%